RNA-interference screen for p53 regulators unveils a role of WDR75 in ribosome biogenesis - Moudry, Pavel; Chroma, Katarina; Bursac, Sladana; Volarevic, Sinisa; Bartek, Jiri (Cell death and differentiation, 2022)
Ribosome biogenesis is an essential, energy demanding process whose deregulation has been implicated in cancer, aging, and neurodegeneration. Ribosome biogenesis is therefore under surveillance of pathways including the p53 tumor suppressor. Here, we first performed a high-content siRNA-based screen of 175 human ribosome biogenesis factors, searching for impact on p53. Knock-down of 4 and 35 of these proteins in U2OS cells reduced and increased p53 abundance, respectively, including p53 accumulation after depletion of BYSL, DDX56, and WDR75, the effects of which were validated in several models. Using complementary approaches including subcellular fractionation, we demonstrate that endogenous human WDR75 is a nucleolar protein and immunofluorescence analysis of ectopic GFP-tagged WDR75 shows relocation to nucleolar caps under chemically induced nucleolar stress, along with several canonical nucleolar proteins. Mechanistically, we show that WDR75 is required for pre-rRNA transcription, through supporting the maintenance of physiological levels of RPA194, a key subunit of the RNA polymerase I. Furthermore, WDR75 depletion activated the RPL5/RPL11-dependent p53 stabilization checkpoint, ultimately leading to impaired proliferation and cellular senescence. These findings reveal a crucial positive role of WDR75 in ribosome biogenesis and provide a resource of human ribosomal factors the malfunction of which affects p53.
Keywords: RNA Precursors; lidé; Ribosomal Proteins; molekuly buněčné adheze; Cell Line, Tumor; ribozomální proteiny; Ribosomes; Humans; Cell Nucleolus; DEAD-box RNA Helicases; jaderné proteiny; ribozomy; Tumor Suppressor Protein p53; buněčné jadérko; nádorový supresorový protein p53; nádorové buněčné linie; DEAD-box RNA-helikasy; prekurzory RNA; Cell Adhesion Molecules; Nuclear Proteins